2018
DOI: 10.1142/s0219749918400075
|View full text |Cite
|
Sign up to set email alerts
|

QUBO formulation for the contact map overlap problem

Abstract: Representing a given problem as a QUBO problem implies the possibility of running it in a quantum computational environment (generic or specific). The well-known problem of looking for similar functions in biological structures, especially of proteins, is of great interest in the field of Bioinformatics. We give a QUBO formulation for CMO protein problem. Experimental results validate this approach as an alternative to classical methods via combinatorial optimization. For the accomplishment of such experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This enhanced connectivity allows for better utilization of the existing qubits, thus fewer vertices are capable of broader calculations. [61]. Simulation results showed that the proposed approach outperformed classical techniques.…”
Section: Related Workmentioning
confidence: 91%
“…This enhanced connectivity allows for better utilization of the existing qubits, thus fewer vertices are capable of broader calculations. [61]. Simulation results showed that the proposed approach outperformed classical techniques.…”
Section: Related Workmentioning
confidence: 91%
“…Although COPs are usually modeled as constrained binary linear programs, solving their QUBO reformulations via a hardware specially designed for QUBOs with the aforementioned aim can indeed outperform solving their natural formulations via an IP solver. Moreover, QUBO problems naturally arise in many applications such as routing (Irie et al 2019;Papalitsas et al 2019), scheduling (Tran et al 2016;Venturelli, Marchand, and Rojo 2015), finance (Elsokkary et al 2017;Orus, Mugel, and Lizaso 2019), and biology (Li et al 2018;Oliveira, Silva, and Oliveira 2018). These problems are more challenging, thus amenable to these new technologies.…”
Section: Solution Methods For Copsmentioning
confidence: 99%
“…Such applications require solving the molecular conformation problem to global optimality [46]. Molecular conformation problem helps predict the native structure of sequence of molecules, and it can be considered as a simplified form of predicting native structures of residues in case of protein folding [39,[47][48][49]. Heuristic solution techniques for the molecular conformation problem are computationally expensive, depend heavily on carefully chosen parameters, and do not guarantee a global optimum [50].…”
Section: Qc For Molecular Conformations In Molecular/product Designmentioning
confidence: 99%